Reduced-order modelling of unsteady vortex lattice method - P Bundith; P Pimanprom; W Janthornsirijan; C Punkun; S Sleesongsom; S Bureerat (My University, 2021)
Abstract The purpose of this research is to present a new idea of reduced-order modelling of unsteady flows without static correction, which is based on fluid eigenmodes. The new reduced order model is formulated based on a new form of wake vortices without static correction. This technique is expected to perform a reduced-order model similar but faster than the previous techniques. The new method is used to analyse unsteady flows over a three-dimensional wing and comparing with the previous techniques. The performances of the present method are demonstrated with numerical examples. The results show the accuracy of the new reduced-order model of unsteady flow with higher computational efficiency. In conclusion, the new method can be considered as an alternative technique to perform the reduced-order models of unsteady flow.
Keywords: Unsteady flow; Turbomachinery Performance and Optimization